Treatment of venous thromboembolism in cancer patients: The dark side of the moon. (May 2021) - Becattini, Cecilia; Di Nisio, Marcello; Franco, Laura; Lee, Agnes; Agnelli, Giancarlo; Mandalà, Mario
Highlights: Venous thromboembolism (VTE) is a common complication in cancer patients. Several international societies released clinical practice guidelines on VTE treatment. We present a critical overview on VTE management in special populations not specifically addressed by international guidelines. Abstract: Venous thromboembolism (VTE) is a common complication in patients with cancer. The risk of emergent VTE is four- to seven-fold higher in cancer patients compared to non-cancer patients. Although the therapeutic armamentarium for cancer-associated VTE has been recently implemented, anticoagulant treatment remains challenging because of the increased risk of recurrent VTE and bleeding. Several international societies and expert panels released clinical practice guidelines on VTE treatment which are mostly focused on the general cancer population. Nevertheless, recommendations for the management of VTE in patients with peculiar clinical presentations are inconsistent and remain elusive due to the lack of pertinent evidence. The challenging clinical scenarios include, among others, patients with thrombocytopenia, renal impairment, gastrointestinal cancer, primary or metastatic brain cancer, distal thrombosis of the lower extremities, catheter-related VTE, splanchnic thrombosis, incidental VTE, extreme body weight, recurrent VTE during treatment, as well as the optimal duration of anticoagulant treatment in patients with active disease who have received 3 to 6 months of anticoagulation. Herein, we present a critical overview on VTE management in these challenging clinical settings, discuss potential approaches, and include some calls to action for future clinical research.